Malawi : Selected Issues. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Selected Issues paper benchmarks Malawi's public spending and identifies areas where there is scope to improve expenditure efficiency. Malawi performs poorly in health and education spending efficiency. Spending in these areas will need to be stepped up to achieve better living standards and higher, more inclusive growth. A rebalancing of the composition of education and health spending-including greater prioritization of low cost-high impact spending and balancing maintenance against capital spending-would yield immediate results in both health and education. Strengthening the public expenditure management chain, especially procurement and supply management, will be important. These reforms would go hand in hand with greater fiscal transparency and accountability in these sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet